NETWORK BUILDING, INNOVATION AREA FOR LEARNING THE BUDDHIST WAY OF LIFE - Saengnont, Kasem; Boonpoo , Somsak; PhrakhruPhattharathammakhun; Mahachano , PhramahaChamnan; Sritragarn , Thongdee; Chaisuk , Prawit; Soktai, Waree (Journal of Educational Review Faculty of Education in MCU, 2024)
The objectives of this research article were to 1) Analyze the network building of the Buddhist learning innovation areas. 2) Develop a model for network building of the Buddhist learning innovation areas. 3) Study and evaluate the results of network building of the Buddhist learning innovation areas. It was qualitative research by studying documents, and group discussion interviews with administrators, teachers, parents, students, temples and communities, and students who were in a network of Buddhist learning innovation areas, 351 people, using small group discussions to confirm the data. There were 13 key informant administrators, faculty, staff, and students in the Faculty of Education and those involved in network building of the Buddhist learning innovation areas. The researcher analyzed the data by focusing on the analysis obtained from summarizing the content, analyzing and synthesizing the data and then writing a descriptive narrative. The results of the research found that: 1) network building of the Buddhist learning innovation areas, including creating inspiration for innovation in the Buddhist way, innovation training, strengthening innovation potential, and promoting investment in innovation. 2) The model for network building of the Buddhist learning innovation areas had 4 dimensions: (1) organizing basic life activities, (2) the working network dimension, (3) the target group dimension creating a collaborative working network, and (4) creating a network of Buddhist innovations. This research emphasized on integration according to the three principles of morality, concentration, and wisdom as a base. Learning through activities to develop students in 4 areas, including social networks, mental network, intellectual network, and the physical network. 3) Evaluate the results of creating a network of Buddhist learning innovation areas. There were 3 phases: the phase before network creation, the implementation phase, and the period after operation.